Dia1-dependent adhesions are required by epithelial tissues to initiate invasion - Fessenden, Tim B.; Beckham, Yvonne; Perez-Neut, Mathew; Ramirez-San Juan, Guillermina; Chourasia, Aparajita H.; Macleod, Kay F.; Oakes, Patrick W.; Gardel, Margaret L. (The Journal of cell biology, 2018)
Developing tissues change shape and tumors initiate spreading through collective cell motility. Conserved mechanisms by which tissues initiate motility into their surroundings are not known. We investigated cytoskeletal regulators during collective invasion by mouse tumor organoids and epithelial Madin–Darby canine kidney (MDCK) acini undergoing branching morphogenesis in collagen. Use of the broad-spectrum formin inhibitor SMIFH2 prevented the formation of migrating cell fronts in both cell types. Focusing on the role of the formin Dia1 in branching morphogenesis, we found that its depletion in MDCK cells does not alter planar cell motility either within the acinus or in two-dimensional scattering assays. However, Dia1 was required to stabilize protrusions extending into the collagen matrix. Live imaging of actin, myosin, and collagen in control acini revealed adhesions that deformed individual collagen fibrils and generated large traction forces, whereas Dia1-depleted acini exhibited unstable adhesions with minimal collagen deformation and lower force generation. This work identifies Dia1 as an essential regulator of tissue shape changes through its role in stabilizing focal adhesions.